Real Time Electrical Load Prediction and Management through Deep Learning and Reinforcement Learning Techniques - Ahmed, Shimaa A.; Khalifa, Entisar H.; Mahmoud, Ashraf F. A.; Abdalla, Faroug A.; Nawaz, Majid; Sulman, Asma (Engineering, Technology & Applied Science Research, 2025)
Real-time electrical load prediction and management are critical to ensuring the stability and reliability of modern power systems, especially as global energy demand continues to grow. This research presents a groundbreaking solution by combining a hybrid deep learning approach with reinforcement learning to address the challenges of accurate forecasting and adaptive energy distribution. The proposed framework integrates Convolutional Neural Networks (CNNs) and Long Short-Term Memory (LSTM) networks, leveraging their strengths to capture both spatial and temporal patterns in electrical load data. This hybrid model delivers highly accurate load forecasts and effectively handles complex and nonlinear consumption patterns that traditional methods fail to address. In addition to accurate forecasting, the research employs the Soft Actor-Critic (SAC) reinforcement learning algorithm, which enables adaptive decision-making for real-time load management. By dynamically adapting to fluctuating grid conditions, the SAC algorithm optimizes energy distribution, reduces peak demand stress, and enhances overall system efficiency. This integrated approach ensures that energy resources are allocated more effectively, improving grid stability and minimizing waste. The methodology is validated through rigorous experimentation using real-world datasets, such as the PJM dataset, and performance metrics, including Mean Absolute Error (MAE), Root Mean Square Error (RMSE), and overall system efficiency. This research not only advances predictive analytics in electrical load management, but also provides utilities and consumers with a scalable and practical solution to optimize energy consumption, integrate renewable energy sources, and promote sustainability. The proposed hybrid deep learning and reinforcement learning framework serves as a vital tool for future energy systems, paving the way for smarter, more resilient power grids.